KEBAHAGIAAN DALAM PERSPEKTIF PSIKOLOGI POSITIF MARTIN SELIGMAN DAN PSIKOLOGI ISLAM - Ani Widiyawati Ani; Nurjannah (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2023)
Every human being definitely expects happiness in his life and in interpreting one's happiness it must be different in one person from another. To find out the meaning of happiness in life, the researcher is interested in researching the meaning of happiness according to Seligman's positive psychology and Islamic psychology. The research used in this study is a type of library research with a qualitative descriptive approach, namely by using content analysis in the study of manuscripts of articles, books and scientific journals then used as a reference. The data source used in this study is a secondary data source. The results of this study mean and happiness in the positive psychology perspective of Martin Seligman is that a person's self-awareness presents positive energy so as to create positive behavior or behavior in the surrounding environment. Whereas in the perspective of Islamic psychology happiness can be achieved by getting closer to Allah SWT such as doing riyadlah, mujahadah, and self-reflection. Happiness in the perspective of positive psychology martin Seligman is a person's self-awareness to present positive energy so as to create positive behavior or behavior in the surrounding environment. Whereas in the perspective of Islamic psychology happiness can be achieved by getting closer to Allah SWT such as doing riyadlah, mujahadah, and self-reflection.